AN ADVANCED TEXTBOOK ON BIODIVERSITY: PRINCIPLES AND PRACTICE - KRISHNAMURTHY, K.V. (New Delhi Oxford & IBH Publishing)
Biodiversity has now become a multidisciplinary subject in which concepts, ideas and methodologies have been contributed by a number of other disciplines. This book presents the concepts, themes and ideas on this ever-growing multi-disciplinary subject.Contents: biodiversity science: definition, scope and constraints / genetic diversity / species diversity: wild taxa / agrobiodiversity and cultivated taxa / ecosystem diversity / values and uses of biodiversity / loss of biodiversity / conservation of biodiversity / management of plant biodiversity / biodiversity and biotechnology / biodiversity prospecting and indigenous knowledge systems / references / glossary / acronyms and abbreviations / subject index / author index
Keywords: Biodiversity